2004
DOI: 10.1038/ng1450
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of a behavioral quantitative trait locus shows that Rgs2 modulates anxiety in mice

Abstract: Here we present a strategy to determine the genetic basis of variance in complex phenotypes that arise from natural, as opposed to induced, genetic variation in mice. We show that a commercially available strain of outbred mice, MF1, can be treated as an ultrafine mosaic of standard inbred strains and accordingly used to dissect a known quantitative trait locus influencing anxiety. We also show that this locus can be subdivided into three regions, one of which contains Rgs2, which encodes a regulator of G prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
227
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(234 citation statements)
references
References 46 publications
6
227
0
1
Order By: Relevance
“…On the long arm of chromosome 6 there is a convergence of linkage for various verbal test measures, and a strong linkage signal on 6p is present for arithmetic. mice where, for instance, a locus influencing anxiety was shown to be composed of three regions, with Rgs2 identified in one of these regions as a modulator of anxiety (Yalcin et al, 2004). The linkage region implicated in our study was most significant for the Cambridge Contextual Reading Test and performance IQ, although empirical p-values indicated reduced linkage to performance IQ.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…On the long arm of chromosome 6 there is a convergence of linkage for various verbal test measures, and a strong linkage signal on 6p is present for arithmetic. mice where, for instance, a locus influencing anxiety was shown to be composed of three regions, with Rgs2 identified in one of these regions as a modulator of anxiety (Yalcin et al, 2004). The linkage region implicated in our study was most significant for the Cambridge Contextual Reading Test and performance IQ, although empirical p-values indicated reduced linkage to performance IQ.…”
Section: Discussionmentioning
confidence: 57%
“…While this method lacks the power of an association analysis, it can implicate chromosomal regions that harbour genes (usually of moderate to large effect) for IQ without the requirement that the genetic markers be the functional polymorphisms or genes extremely close by (Vink and Boomsma, 2002). Furthermore, it has been shown that the clustering of QTLs of small effect in the same region can produce a linkage signal of relatively large effect (Legare et al, 2000;van Wezel et al, 1999;Yalcin et al, 2004). Like association analysis, though, replication of QTLs identified using whole genome methods is essential given the multiple testing of markers.…”
Section: Introductionmentioning
confidence: 99%
“…RGS2 knockout has been found to decrease aggression in mice (Oliveira-Dos-Santos et al, 2000). In addition, an analysis of a behavioral quantitative trait locus in mouse showed that RGS2 modulated anxiety (Yalcin et al, 2004). In animals and humans, the amygdala is believed to control emotions such as fear and anxiety and behaviors such as impulsive violence (Phelps and LeDoux, 2005;Shaikh et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…RGS2-deficient mice displayed an increased anxiety response and decreased aggression (Oliveira-Dos-Santos et al, 2000). The genetic dissection of a behavioral quantitative trait locus study showed that RGS2 modulated anxiety in mice (Yalcin et al, 2004). Moreover, RGS2 gene polymorphisms have recently been associated with panic disorder (Leygraf et al, 2006), thus suggesting that RGS2 modulates anxiety not only in mice but also in humans.…”
Section: Introductionmentioning
confidence: 99%
“…10 RGS2, a 211 aminoacid protein, influences several major receptor signaling systems in the central nervous system including dopaminergic, 11 serotonergic, 12 cholinergic 13 and opioid 14 receptors. Involvement of RGS2 in conditions, such as anxiety 15 and hypertension 16 has been suggested and an association of the gene with panic disorder has been reported. 17 Since replication studies are essential in the field of pharmacogenetics, we report a further evaluation of our initial findings concerning the association of RGS2 with AIP in a sample of schizophrenia patients from the United States treated with typical and atypical antipsychotics drugs.…”
Section: Introductionmentioning
confidence: 99%